Production of Biodiesel form Annona Muricata Seeds - Wong, Wai Leong (Universiti Teknologi PETRONAS, 2017)
Biodiesel is one of the effective alternative fuels to overcome the problems associated with environmental issues and energy crisis. However, the production of biodiesel from edible oil has provoked the food versus fuel dispute. Thus, non-edible crops, the Annona Muricata seed is selected as the raw material to produce oil for biodiesel production. In this study, Annona Muricata oil was extracted with n-hexane at the temperature of 70 ℃ for 6 hours. Subsequently, the oil was transesterified with methanol and potassium hydroxide (KOH) to produce biodiesel. The significance of transesterification parameters including the temperature, time, catalyst concentration and oil to methanol ratio on the biodiesel yield (%) as well as oleic acid (%) was established through two-level factorial design.